THE EFFECT OF INTELLECTUAL CAPITAL, CAPITAL STRUCTURE, EARNING PER SHARE AND PROFITABILITY ON STOCK PRICES WITH PRICE EARNING RATIO AS MODERATION VARIABLES IN LQ45 COMPANIES IN INDONESIA STOCK EXCHANGE - Arvila, Tasyah (Asosiasi Dosen Akuntansi Indonesia, 2021)
This study aims to determine the effect of Intellectual Capital, Capital Structure, Earning Per Share, and Profitability on Stock Prices at LQ45 companies on the Indonesia Stock Exchange. In addition, this study also aims to determine whether Price Earning Ratio can be used as a moderating variable in the model. The research design carried out is a causal associative research study. The samples in this study were 34 LQ45 companies listed on the Indonesia Stock Exchange in 2015 to 2018. The type of data used in this study is secondary data types. And data analysis techniques using multiple linear regression analysis and interaction testing (moderating) conducted with the help of software Eviews 9. The results in this study indicate that partially earnings per share and profitability have a positive and significant effect on stock prices. However, intellectual capital and capital structure have no significant effect on stock prices. As well as other results that show that Price Earning Ratio can strengthen the Earning Per Share relationship and Profitability to stock prices. However, Price Earning Ratio is not a moderating variable in the effect of intellectual capital and capital structure on stock prices in LQ45 companies on the Indonesia Stock Exchange.